PELATIHAN PENYUSUNAN PTK BAGI GURU SD DI KECAMATAN SECANG - Athia Fidian; Agrissto Bintang Aji Pradana (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2020)
Abstract:The 2009 Permenpan-RB on Sustainable Professional Development is not only aimed at PNS teachers but teachers in general. Members of the GTT-PTT Honorary Staff Forum at Secang District have a strong desire to be able to arrange the classroom action research (CAR). However, this desire is constrained by the limited opportunities given to them attending CAR training. Most of them do not have enough knowledge about CAR preparation. In addition to being unfamiliar with research methods, they also lack knowledge of how to plan and compile their reports. Seeing this problem, this dedication activity became a concrete effort to help teachers, especially members of the Secang GTT-PTT Honorary Forum at Secang District, to provide training and mentoring for the preparation of CAR increasing the knowledge about CAR development. This community service was carried out within 4 months. This activity was attended by 25 participants. The method of activities carried out to resolve partner problems was through training and mentoring divided into 5 meetings at the SDN 2 Secang hall. Material presented at the first meeting were: (1) PTK concept; (2) preparation of background, problem identification and formulation of topics and problems; (3) looking for sources of reference related to the topic, as well as the design of the CAR implementation; (4) preparation of results and discussion; and (5) finalization of the report.        Keywords:Community Services, Training, Action Research  Abstrak: Permenpan-RB Tahun 2009 tentang Pengembangan Keprofesian Berkelanjutan (PKB) tidak hanya ditujukan kepada guru PNS saja namun guru secara umum. Anggota Forum Tenaga Honorer GTT-PTT Kecamatan Secang memiliki keinginan yang kuat untuk mampu menyusun PTK. Namun, keinginan tersebut terkendala dengan terbatasnya kesempatan yang diberikan kepada mereka untuk mengikuti pelatihan PTK. Sebagian besar dari mereka tidak memiliki pengetahuan yang cukup mengenai penyusunan PTK. Selain awam dengan metode penelitian, mereka juga tidak memiliki pengetahuan tentang bagaimana merencanakan dan menyusun laporannya. Melihat masalah tersebut, kegiatan pengabdian ini menjadi upaya konkret dalam membantu guru terutama anggota Forum Tenaga Honorer GTT-PTT Kecamatan Secang untuk memberikan pelatihan dan pendampingan penyusunan PTK dalam meningkatkan pengetahuan tentang penyusunan PTK. Pengabdian masyarakat ini dilaksanakan dalam waktu 4 bulan. Kegiatan ini diikuti oleh 25 peserta. Metode kegiatan yang dilaksanakan guna menyelesaikan permasalahanmitra adalah dengan pelatihan dan pendampingan yang dibagi menjadi 5 pertemuan bertempat di aula SDN 2 Secang. Materi yang disampaikan dalam pertemuan pertama adalah: (1) konsep PTK; (2) penyusunan latar belakang, identifikasi masalah serta perumusan topik dan masalah; (3) mencari sumber rujukan terkait topik, serta desain pelaksanaan PTK; (4) penyusunan hasil dan pembahasan; dan (5) finalisasi laporan. Kata kunci : Pengabdian Masyarakat, Pelatihan, Ptk